Pengaruh Harga Tiket Penerbangan terhadap Minat Wisatawan di Manado Sulawesi Utara Menggunakan Jasa Transportasi Udara - Moh Fajrul Mubaraq; Aditya Dewantari (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
Tourism is an important sector for the economy, where Sam Ratulangi International Airport Manado acts as the main connectivity hub connecting domestic and international tourists. In 2024, the number of foreign tourist visits through this airport was recorded at 45,884 people, a decrease of 49.3% compared to the previous year according to BPS data, while domestic tourist visits actually increased significantly to 743,948 people. This phenomenon shows the great potential for tourism in Manado, but also challenges related to fluctuations in the number of tourists, especially from abroad. This study aims to determine the effect of flight ticket prices on tourist interest in using air transportation services in Manado, North Sulawesi in using air transportation services, and to measure how much influence flight ticket prices have on the interest of tourists in Manado, North Sulawesi in using air transportation services. This study uses a quantitative correlational method involving 100 tourist respondents visiting Manado. The sampling technique uses probability sampling with simple random sampling technique. Data analysis is carried out using. validity test, reliability test, normality test, linearity test, simple linear regression, T test and coefficient of determination (R2). Data processing through the SPSS version 22.0 application. The results of the study from the statistical test results showed a T count value of 4.945 which is greater than the t table of 1.660, and a significance value of 0.000 which is smaller than the probability of 0.1. It is known that the correlation or relationship value (R) is 0.447 and the coefficient of determination value is 0.200, which means that the influence of the flight ticket price variable on tourist interest is 20.0%. Meanwhile, the remaining 80.0% is influenced by other factors not examined in this study, such as promotion, facilities, or destination appeal. Thus the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected, which means that there is a significant influence between flight ticket prices and tourist interest.